Answer:
Part 1) Equation of a perpendicular line is [tex]y=\frac{2}{3}x+4[/tex]
Part 2) Equation of a parallel line is [tex]y=-\frac{3}{2}x+\frac{21}{2}[/tex]
Step-by-step explanation:
Part 1) Find the equation of the line that is perpendicular to the given line and passes through the point (3, 6).
we have
[tex]y=-\frac{3}{2}x-3[/tex]
The slope of the given line is [tex]m=-\frac{3}{2}[/tex]
Remember that
If two lines are perpendicular, then their slopes are opposite reciprocal (the product of the slopes is equal to -1)
so
The slope of the perpendicular line to the given line is equal to
[tex]m=\frac{2}{3}[/tex]
Find the equation of the line in point slope form
[tex]y-y1=m(x-x1)[/tex]
we have
[tex]m=\frac{2}{3}[/tex]
[tex]point\ (3,6)[/tex]
substitute
[tex]y-6=\frac{2}{3}(x-3)[/tex]
Convert to slope intercept form
[tex]y=mx+b[/tex]
Isolate the variable y
[tex]y-6=\frac{2}{3}x-2[/tex]
[tex]y=\frac{2}{3}x-2+6[/tex]
[tex]y=\frac{2}{3}x+4[/tex]
Part 2) Find the equation of the line that is parallel to the given line and passes through the point (3, 6).
we have
[tex]y=-\frac{3}{2}x-3[/tex]
The slope of the given line is [tex]m=-\frac{3}{2}[/tex]
Remember that
If two lines are parallel, then their slopes are the same
so
The slope of the parallel line to the given line is equal to
[tex]m=-\frac{3}{2}[/tex]
Find the equation of the line in point slope form
[tex]y-y1=m(x-x1)[/tex]
we have
[tex]m=-\frac{3}{2}[/tex]
[tex]point\ (3,6)[/tex]
substitute
[tex]y-6=-\frac{3}{2}(x-3)[/tex]
Convert to slope intercept form
[tex]y=mx+b[/tex]
Isolate the variable y
[tex]y-6=-\frac{3}{2}x+\frac{9}{2}[/tex]
[tex]y=-\frac{3}{2}x+\frac{9}{2}+6[/tex]
[tex]y=-\frac{3}{2}x+\frac{21}{2}[/tex]